2018
DOI: 10.21037/tlcr.2018.06.01
|View full text |Cite
|
Sign up to set email alerts
|

Inherited lung cancer syndromes targeting never smokers

Abstract: Lung cancer is the leading cause of cancer death worldwide. Most of lung cancers develop sporadically and thus inherited lung cancers are rare. Several reports show that germline mutations in the kinase domain of epidermal growth factor receptor () such as R776G, R776H, T790M, V843I and P848L, predispose to develop lung cancer. Most lung cancer cases with germline T790M mutations had secondary somatic mutations. Never smokers with germline T790M mutations develop lung cancer more frequently than ever smokers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 59 publications
4
34
0
1
Order By: Relevance
“…In addition to somatic mutations, other reported EGFR-associated mechanisms for inherent resistance to EGFR-TKIs are the germline T790M polymorphism in exon 20 and the germline V843I mutation in exon 21 [113,114,115]. NSCLCs with germline T790M or V843I mutations are predominantly LACs harboring a secondary somatic classic EGFR -mutation and occur more frequently in females and non-smokers [115]. The families harboring the T790M or V843I mutations are predisposed to NSCLC development as these mutations contribute to tumorigenesis by promoting phosphorylation of EGFR and its downstream signaling proteins.…”
Section: Clinical and Preclinical Studies Shedding Light On Intrinmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to somatic mutations, other reported EGFR-associated mechanisms for inherent resistance to EGFR-TKIs are the germline T790M polymorphism in exon 20 and the germline V843I mutation in exon 21 [113,114,115]. NSCLCs with germline T790M or V843I mutations are predominantly LACs harboring a secondary somatic classic EGFR -mutation and occur more frequently in females and non-smokers [115]. The families harboring the T790M or V843I mutations are predisposed to NSCLC development as these mutations contribute to tumorigenesis by promoting phosphorylation of EGFR and its downstream signaling proteins.…”
Section: Clinical and Preclinical Studies Shedding Light On Intrinmentioning
confidence: 99%
“…Like T790M, the V843I mutation is associated with familial clustering of NSCLC and appears to provide resistance to EGFR-TKIs through structural modification of EGFR that sterically hinders TKI binding [113,114]. Thus, cases with germline T790M or V843I mutations could be categorized as a class of familial lung cancer syndrome with resistance to 1G/2G EGFR-TKIs but possibly sensitive to 3G TKIs [114,115].…”
Section: Clinical and Preclinical Studies Shedding Light On Intrinmentioning
confidence: 99%
“…In this study, we showed that KP-LC vaccine evokes anti-tumor T cell responses using both subcutaneous tumor and induced transgenic models of disease ( Figure 6A ) and significantly extended the survival time of KP-LC vaccinated mice, although notably did not prevent disease related death. This suggests scope for improvement of the regime, that should include optimizing the number of prime-boost cycles applied to the patient and more specific tailoring of iPSCs by introduction of other driver mutations, particularly those associated with genetic inheritance, including EGFR amongst others ( 37 ). It is worth noting that vaccination produced by the lung cancer cell line KP-LC derived from iPS cells or the lung cancer cell line KPL 160302S derived from early lung cancer models can both significantly prolong the survival of lung cancer mice, and their effect on CD8+ T cells and CD4+ T cells infiltration are similar.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous other EGFR-related mutations associated with resistance mechanisms, such as the EGFR P848L mutation ( 18 22 ), EGFR amplification ( 23 , 24 ), MET amplification ( 25 , 26 ), HER2 mutations ( 27 , 28 ), PIK3CA mutations ( 29 – 31 ) and mutations activating the RAS-MAPK signalling pathway ( 32 35 ). The present study revealed that a patient with the EGFR21L858R, P848L/T790M mutations experienced rapid progression after TKI treatment, including osimertinib.…”
Section: Discussionmentioning
confidence: 99%